2013
DOI: 10.1055/s-0032-1333236
|View full text |Cite
|
Sign up to set email alerts
|

Association of Ethnicity with Antipsychotic Dosage Using STRUCTURE Analysis

Abstract: Several studies have examined whether ethnicity as an independent factor can influence the individual's dosage of antipsychotics. However, there has been inconsistency in the results of these studies, particularly between white and non-white populations. This retrospective study tests the hypothesis of different dosing of antipsychotics in white Europeans vs. non-white Europeans considering both the self-reported ethnicity and the geographical ancestry calculated using 196 DNA markers.We collected self-reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…[6] A prolonged DUP may indicate the need for higher doses of antipsychotics, but ethnicity has been seen not to be a factor in determining DUP. [7] With respect to variations in prescribing practices which are based on ethnic variations, some studies did find that such differences did exist. [8,9] Whilst other studies showed that antipsychotic prescribing practice did not differ between patients from the Black and White ethnic groups.…”
Section: T He Phy S I Ci Anmentioning
confidence: 99%
See 1 more Smart Citation
“…[6] A prolonged DUP may indicate the need for higher doses of antipsychotics, but ethnicity has been seen not to be a factor in determining DUP. [7] With respect to variations in prescribing practices which are based on ethnic variations, some studies did find that such differences did exist. [8,9] Whilst other studies showed that antipsychotic prescribing practice did not differ between patients from the Black and White ethnic groups.…”
Section: T He Phy S I Ci Anmentioning
confidence: 99%
“…[4] However a similarly sized study comparing antipsychotic dosing of all antipsychotics using chlorpromazine-equivalent calculations in white Europeans compared to non-white Europeans found no significant differences using both self -reported ethnicity and geographical ancestry determined by DNA sample. [7] The contradictions between these studies could perhaps be explained by the different approaches: homing in on individual medications sharpens the focus on ethnic differences in response to that treatment which is lost when comparing with many other drugs all at once. Alternatively given that the interplay between genes and environment is notoriously complex, there may also be differences in European responses compared with those from other continents.…”
Section: Ethnic Differences In Treatment Outcomes In Psychosismentioning
confidence: 99%